‘Battle of Evermore’: A Treatise on the Theater of Transcendence - Osai, Jason O (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
The paper studies the essence and doctrinaire interpretation of ‘transcendence’ from the religious perspective covering the creeds of Judaism, Hinduism, Buddhism, Christianity, Islam, Sikhism and Baha’i. The paper also reviews the philosophical roots of ‘transcendence’ discussing its original definition, the medieval usage, colloquial usage, transcendent theosophy and the Kantian and modern philosophy of transcendence within which the views of Socrates, Plato, David Hume, Mulla Sadra, Jean-Paul Sartre and Stephen Palmquist, were brought to bear on the discourse. Essentially, the paper contends that there is an eternal scuffle that is taking place between higher and lower forces and the main arena of this struggle is in the human mind as encased in the human body. The paper furthers that in every individual, there is the tri-unity of the senses, the soul and the spirit. The senses are as imbedded in the human body with the sense of touch, taste, sight, sound and smell; the soul is the essence of man’s existence here on earth while the spirit is a spark of God in human. In its journey on earth, the soul continually utilizes the mind in choosing between the essence of the soft whispers of the spirit and the compelling demands of the senses. The soul is, therefore, constantly caught between these two forces; and this is what is dubbed the Battle of Evermore. The author holds that this second-by-second non-violent eternal conflict takes place in all human beings irrespective of color or creed and station or location on earth. Ascendancy in the single super consciousness of the ethereal is a direct product of the cumulative of the degree to which the soul defeats the compulsions of the senses. That, the paper concludes, is the essence of transcendence. Key Words:*Transcendence, *Human mind, *Senses, *Soul, *Spirit, *Philosophical perspective, *Religious perspective, *Transcendent theosophy, *The end of transcendence, *Personal enterprise, *Universal phenomenon.